LOYALITAS NASABAH DI PT. BANK RAKYAT INDONESIA KCP KOTA WISATA KABUPATEN BOGOR DITINJAU DARI KUALITAS PRODUK, PROMOSI DAN KUALITAS PELAYANAN - Ibnu Haris Nasution; Agtovia Frimayasa (Fakultas Bisnis dan Ilmu Sosial Universitas Dian Nusantara, 2022)
This study aims to see how the influence of product quality, promotion and service quality on customer loyalty at Bank BRI KCP Kota Wisata Bogor Regency. The form of the research is associative with the population being all customers who are savers at the BRI KCP bank, Bogor Regency, which amount to 10,000 customers. Sampling with the slovin formula to obtain a sample of 200 customers. The measurement of the variables was done by using a questionnaire which was quantified with a Likert scale. The method of analysis is carried out by stratified regression. This is intended to see the relationship of variables to other variables directly or indirectly or through intermediate variables. Based on the existing phenomenon, BRI KCP Kota Wisata Bogor Regency from time to time has increased the number of customers every year. This research is a type of field research that uses quantitative methods. The type of data used in this research is the type of primary data assisted by the SPSS program. Data collection was taken from the results of distributing questionnaires to 100 respondents. The sampling technique used in this study is the Accidental Sampling method and this study uses multiple linear regression data analysis techniques. The results of this study indicate that the product quality variable partially has no effect on customer loyalty, while the promotion variable and service quality variable partially have a positive and significant effect on customer loyalty at PT. Bank BRI KCP Kotawisata, Bogor Regency.